Ecophysiology of syntrophic communities that degrade saturated and unsaturated long-chain fatty acids - Sousa, D. Z. (2009)
Syntrophic relationships are the key for biodegradation in methanogenic environments. We review the ecological and physiological features of syntrophic communities involved in the degradation of saturated and unsaturated long-chain fatty acids (LCFA), as well as their potential application to convert lipids/fats containing waste to biogas. Presently, about 14 species have been described with the ability to grow on fatty acids in syntrophy with methanogens, all belonging to the families Syntrophomonadaceae and Syntrophaceae. The principle pathway of LCFA degradation is through β-oxidation, but the initial steps in the conversion of unsaturated LCFA are unclear. Communities enriched on unsaturated LCFA also degrade saturated LCFA, but the opposite generally is not the case. For efficient methane formation, the physical and inhibitory effects of LCFA on methanogenesis need to be considered. LCFA adsorbs strongly to biomass, which causes encapsulation of active syntrophic communities and hampers diffusion of substrate and products in and out of the biomass. Quantification of archaea by real-time PCR analysis suggests that potential LCFA inhibitory effect towards methanogens might be reversible. Rather, the conversion of adsorbed LCFA in batch assays was shown to result in a significant increase of archaeal cell numbers in anaerobic sludge samples.